2020
DOI: 10.1002/mc.23236
|View full text |Cite
|
Sign up to set email alerts
|

Loss of prdm1a accelerates melanoma onset and progression

Abstract: Melanoma is an aggressive, deadly skin cancer derived from melanocytes, a neural crest cell derivative. Melanoma cells mirror the developmental program of neural crest cells in that they exhibit the same gene expression patterns and utilize similar cellular mechanisms, including increased cell proliferation, EMT and migration. Here we studied the role of neural crest regulator PRDM1 in melanoma onset and progression. In development, Prdm1a functions to promote neural crest progenitor fate, and in melanoma, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
5
1
Order By: Relevance
“…MCR:SATB2 transgenic animals, in addition to developing tumors faster, had a high prevalence of tumor burden in internal organs, which is uncommon in MCR:EGFP controls, even in animals with very large tumors (Figure 1D-G, Supplementary Figure 1D-E). This has not been previously observed with several other accelerators or drug resistance drivers that we and others have identified using the MiniCoopR model (Ablain et al, 2018; Ceol et al, 2011; Dang et al, 2016; Fazio et al, 2020; Iwanaga et al, 2020; Kaufman et al, 2016; Venkatesan et al, 2018).…”
Section: Discussioncontrasting
confidence: 65%
“…MCR:SATB2 transgenic animals, in addition to developing tumors faster, had a high prevalence of tumor burden in internal organs, which is uncommon in MCR:EGFP controls, even in animals with very large tumors (Figure 1D-G, Supplementary Figure 1D-E). This has not been previously observed with several other accelerators or drug resistance drivers that we and others have identified using the MiniCoopR model (Ablain et al, 2018; Ceol et al, 2011; Dang et al, 2016; Fazio et al, 2020; Iwanaga et al, 2020; Kaufman et al, 2016; Venkatesan et al, 2018).…”
Section: Discussioncontrasting
confidence: 65%
“…To validate it, we collected experimental datasets and found that the expression level and ssGSEA score of the CD8+ T exhausted specific signature were reduced in CD8+ tumor-infiltrating lymphocytes of Prdm1 cKO mice compared to wild type ( Figures S4C,D ). A recent study also demonstrated that PRDM1 is essential for the differentiation of melanoma and its high expression level indicates better survival in melanoma ( 50 ). In particular, for IFNG ligand, interferon-gamma treatment could induce increased activity of the tumor intermediate state in 48 melanoma cell lines ( Figure 6C , Wilcoxon rank-sum test).…”
Section: Resultsmentioning
confidence: 98%
“…Melanoma cells show similarity of build in developmental program with neural crest cells and exhibit the same gene expression patterns. Findings of a novel study demonstrated that loss of neural crest regulator- highly conserved transcriptional factor PRDM1 accelerates the development of melanoma and confirmed its role of tumor suppressor in p 53 muted models [62] . Other study validating in those in vitro and in vivo experiments, oncogene- induced (BRAF V600E ) senescence presents a genuine protective physiological process and senescent proliferation of melanocytes also leads to a benign in the form of nevi or moles [63] .…”
Section: Biology Of Melanoma Skin Cancermentioning
confidence: 85%